Extending improvements of eutrophication and water quality via induced natural mixing after artificial mixing in a stratified reservoir. (15th November 2022) - Wen, Chengcheng; Li, Kai; Huang, Tinglin; Wang, Sai; Tang, Yun; Wen, Gang; Zhang, Haihan; Li, Xiaohua; Cai, Xiaochun
Abstract: Induced (natural) mixing proposed by our teams can solve a big problem of low-energy water situation improvement of stratified reservoirs by minimizing operating periods of water-lifting aerators (WLAs) to advance a complete natural mixing. Here, the mechanisms influencing water situation via induced mixing were systematically explored using a combination of multi-water-environment assessment methods including trophic level index (TLI), water quality index (WQI), and minimum WQI (WQImin ) based on long-term field data (i.e., non-operational and operational years of WLAs). The results showed that induced mixing after WLA deactivation improved the levels of eutrophication and water quality (into "light-eutrophic" and "good" status) with a decrease in TLI values (56.0–56.2) and increase in WQI (79.0–79.9) and WQImin (81.5–89.3) values, compared to mixing of the non-operational year (TLI: 69.6, WQI: 73.4, WQImin : 76.1). Induced mixing was launched by deactivating the WLAs in cooling seasons (i.e., in late September within a subtropical monsoon climate zone), which advanced and prolonged the periods of naturally complete mixing by 2–3 months. Water temperature (WT), Dissolved oxygen (DO), relative water column stability (RWCS) and inflow were primary drivers for the water situation succession in the study years. Induced mixing extended the well-oxygenated and mixed conditions (temperature difference <1.0 °C, DO > 8.5 mg/L, RWCS< 20) following artificial mixing to improve the water status from single index level (improvement of 18.8%–73.7% than mixing before the operational years) to integrated evaluation results by changing WT, DO, and RWCS. This study presents a successful case for energy-saving pollution control using mixing systems. Graphical abstract: Image 1 Highlights: Induced natural mixing was proposed to achieve low-energy water status improvement. A naturally complete mixing was extended by 2.2 times using a mixing system (WLAs). Temperature, oxygen, water stability (RWCS), and inflow affected water situation. Induced natural mixing improved water status by changing temperature, oxygen, RWCS. WLA deactivation in proper conditions can advance/extend a naturally complete mixing.